MODERN TECHNOLOGICAL POSSIBILITIES OF ETIOLOGICAL DIAGNOSTICS OF SEPSIS - Nabieva Farangiz Sadriddinovna; Aliqulov Samariddin Sirojiddin O’g’li; Suyunova Maftuna Shokir Qizi (Journal of new century innovations, 2023)
Annotation. Sepsis is currently considered to be the result of an uncontrolled systemic inflammatory response (generalized inflammatory response) to the presence of an infection. Diagnosis of sepsis includes the identification of an etiological infectious factor - the identification of the pathogen and the study of its sensitivity to antibacterial drugs, since it is the use of appropriate antibiotics that, ceteris paribus, is the key to the final cure of the patient.